2020
DOI: 10.21203/rs.3.rs-44361/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-target screening for detecting the occurrence of plant metabolites in river waters

Abstract: Background: In surface waters, using liquid chromatography coupled to high resolution mass spectrometry (LC-HRMS), typically large numbers of chemical signals often with high peak intensity remain unidentified. These chemical signals may represent natural compounds released from plants, animals and microorganisms, which may contribute to the cumulative toxic risk. Thus, attempts were made to identify natural compounds in significant concentrations in surface waters by identifying overlapping LC-HRMS peaks betw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This demonstrates that for I. glandulifera , although already being evaluated as an invasive plant by governmental institutions, a comprehensive understanding of the far‐reaching impacts across ecosystem‐boundaries has still not been fully achieved. Recent studies showed that natural waterbodies may contain a cocktail of other phytotoxins, like coumarins, formononetin and alkaloids in concentrations of up to 90 µg/L (Günthardt et al, 2021; Nanusha et al, 2020, 2021; Nanusha, Krauss, Schönsee, et al, 2020), which may act synergistically, and further amplify the effects of low doses of 2‐MNQ on aquatic ecosystems. Our study paves the way to better assess the hazard of invasive terrestrial plant species on aquatic ecosystems under both: natural‐like and laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that for I. glandulifera , although already being evaluated as an invasive plant by governmental institutions, a comprehensive understanding of the far‐reaching impacts across ecosystem‐boundaries has still not been fully achieved. Recent studies showed that natural waterbodies may contain a cocktail of other phytotoxins, like coumarins, formononetin and alkaloids in concentrations of up to 90 µg/L (Günthardt et al, 2021; Nanusha et al, 2020, 2021; Nanusha, Krauss, Schönsee, et al, 2020), which may act synergistically, and further amplify the effects of low doses of 2‐MNQ on aquatic ecosystems. Our study paves the way to better assess the hazard of invasive terrestrial plant species on aquatic ecosystems under both: natural‐like and laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%